AN ANALYSIS OF BTS’S SELECTED SONG LYRICS: A STUDY OF DENOTATIVE, CONNOTATIVE AND MYTH MEANING - Nabila, Indah; Thamrin, Husni; Supian, Supian; Rusmana, Erik (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
This Research is entitled “An Analysis of BTS’s Selected Song Lyrics: A Study of Denotative, Connotative and Myth Meaning”. The study is conducted to look at the meaning namely denotation and connotation as well as myth in these selected songs. The writer limits the research to only focus on 3 selected BTS songs. The writer used Roland Barthes’s theory. By using the method, the meaning contained in the song lyrics can be described in detail by analyzing the meaning of denotation and connotation in the lyrics and also to find the myths about what is already formed. The writer uses a descriptive qualitative method in order to answer the research problem. The writer found that there are 9 sign systems for BTS Epilogue: Young Forever lyrics that regarding career pressures or a person's mental health condition particularly for K-pop idols, 9 sign systems for BTS Fire lyrics that relate to social class, especially in Korea that usually called spoon theory and 12 sign systems for BTS ON lyrics that show how the shadow self- began to appear